Study of the cell surface proteome for the analysis of Parkinson’s disease associated DJ-1 mutations - Jordão, Nuno Ricardo de Oliveira (2018)
Parkinson’s disease (PD) is a neurodegenerative disease, characterized with selective neurodegeneration and dopamine depletion. Despite most cases appear to have sporadic origin, it has been associated various monogenic mutations to the onset of a parkinsonian phenotype. DJ-1 protein is of particular interest given its neuroprotective role against oxidative stress and mitochondria impairment, and the identification of several mutations correlated with early onset PD. For this study, it were then produced two pathological mutations of DJ-1, M26I and E163K. SDS-PAGE and LC-MS/MS analysis confirmed the adequate production and purification of the both mutant proteins, and SEC-HPLC secured the structural perseverance of the mutations as homodimers, a key feature of DJ-1 essential for its biological activity. On the other hand, SH-SY5Y viability assays indicated that despite the native form protective role against oxidative stress, M26I and E163K mutations showed a compromised neuroprotective capacity. To better understand the reasons for this biological impairment, it was developed a protocol for cell surface proteins labelling with Sulfo-NHSLC-biotin and avidin pull-down for enrichment and downstream MS analysis. Assays such as western blotting, LC-MS/MS and confocal microscopy confirmed the adequacy of the proposed procedure. When applied for the analysis of proteome variations related to oxidative stress, in enriched fractions from SH-SY5Y biotinylation and avidin pull-down of crude membrane sub cellular part, it allowed the identification of several proteins of interest, namely four proteins with significant difference caused by oxidative stress induction, and of other proteins of interest. It was also performed the direct pull-down of whole protein extract, offering inconclusive results regarding the preferential use of ultracentrifugation before pull-down. Nevertheless, it was the first time that SH-SY5Y cell surface was analysed in a PD context, and it could be used in the future to study cell surface proteome alterations modulated by oxidative stress and extracellular presence of native or mutant DJ-1, providing new insights regarding its intake and signalling modulation in pathological conditions, and hence contributing for a new perspective over preventive or eliciting mechanisms associated to the onset of Parkinson’s disease.